2010
DOI: 10.2131/jts.35.41
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Centella asiatica extract (CAE) on experimentally induced parkinsonism in aged Sprague-Dawley rats

Abstract: -Reactive oxygen species (ROS) play an important role in ageing and age-related neurodegenerative changes including Parkinson's disease (PD). PD is characterized by signs of major oxidative stress and mitochondrial damage in the pars compacta of the substantia nigra. Present study was designed to investigate whether the Centella asiatica extract (CAE) would prevent 1-methyl-4-phenyl-1,2,3,6 -tetrahydropyridine (MPTP) -induced neurotoxicity in aged Sprague-Dawley rats. Adult, male Sprague-dawley rats of 300-350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 42 publications
3
42
0
1
Order By: Relevance
“…MPTP is typically administered systemically in mice because it is able to cross the BBB (Cannon and Greenamyre, 2010). Although rats are resistant to MPTP for unknown reasons, they were also used in some studies (Yang et al, 2001;Fujikawa et al, 2005b;Haleagrahara and Ponnusamy, 2010). Rotenone, which produces systemic complex I inhibition, is often chronically systemic administered in rats (Fujikawa et al, 2005a;Sanchez-Reus et al, 2007).…”
Section: Neurotoxic In Vitro and In Vivo Models Used To Test Herbal Mmentioning
confidence: 99%
“…MPTP is typically administered systemically in mice because it is able to cross the BBB (Cannon and Greenamyre, 2010). Although rats are resistant to MPTP for unknown reasons, they were also used in some studies (Yang et al, 2001;Fujikawa et al, 2005b;Haleagrahara and Ponnusamy, 2010). Rotenone, which produces systemic complex I inhibition, is often chronically systemic administered in rats (Fujikawa et al, 2005a;Sanchez-Reus et al, 2007).…”
Section: Neurotoxic In Vitro and In Vivo Models Used To Test Herbal Mmentioning
confidence: 99%
“…It also has protective effects against neurotoxixity. These effects of AA have been shown in stroke and some degenerative neurodisorders such as Parkinsonism and Alzheimer Disease (7,10,12).…”
Section: Interleukin 1βmentioning
confidence: 97%
“…These are flavonoids, triterpenes and polyacetylenes. Some of the triterpenoids compounds are madecassoside, madecassic acid, asiaticoside, and AA (7,14).…”
Section: Interleukin 1βmentioning
confidence: 99%
“…Aqueous extract of C. asiatica on intra cerebrovascular streptozocin-induced memory associated with the sporadic type of Alzheimer's disease and pentylenetetrazoleinduced memory loss in rats showed the increasing neuroprotection through suppression of malondialdehyde and increasing antioxidant enzyme catalase, superoxide dismutase and glutathione [51,52] . Another experiment showed that C. asiatica protects rotenone-induced cells through the stabilization of mitochondrial membrane potential and inhibiting voltage-dependent anion channel enzyme [34,35]. It seems that antioxidant and anti-inflammatory property of C. asiatica could protect rotenone-induced zebrafish motility through the stabilization of dopamine synthesis, availability and its kinetics.…”
Section: Dopamine Level and A-synuclein Aggregationmentioning
confidence: 99%
“…This condition may be caused by antioxidant and anti-inflammatory property of C. asiatica [33]. Haleagrahara and Ponnusamy [34] reported that supplementation of C. asiatica decreased lipid hydroperoxide, protein carbonyl content, and significantly increased total antioxidant and antioxidant enzyme level in rat induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine. Asiatic acid, one of the major components in C. asiatica could protect rotenone-induced SH-SY5Y cell through the stabilization of mitochondrial membrane potential, decreasing voltagedependent anion channel both in mRNA and protein level [35].…”
Section: Motility Assessmentmentioning
confidence: 99%